Spatial Assessment of Land Degradation Risk for the Okavango River Catchment, Southern Africa - Weinzierl, Thomas; Wehberg, Jan; Böhner, Jürgen; Conrad, Olaf (Land degradation & development, 2016)
The Okavango catchment in southern Africa is subject to environmental as well as socio‐economic transformation processes such as population growth and climate change. The degradation of soil and vegetation by deforestation and overgrazing is one of the downsides of this development, reducing the capacity of the land to provide ecosystem functions and services. In this study, climate simulations are brought together with secondary socioeconomic, pedologic and remote‐sensing data in a GIS‐based assessment of the factors commonly associated with land degradation risk. A high resolution overview is provided for decision‐makers and stakeholders in the region by identifying priority intervention areas where a long‐term decline in ecosystem function and land productivity is most likely to occur. The approach combines 19 risk factors into seven individual ratings for topography, landcover, soil, demography, infrastructure, livestock pressure and climate. These ratings are then weighted and combined into an integrated degradation risk index (DRI). The results show that the land degradation risk is quite heterogeneously distributed in the study area and caused by different factors. Three hot‐spots are identified and compared, one of which is in the far northwestern part of the catchment, one around the local center Rundu and one on the outskirts of the Okavango Delta. We conclude that the approach is suitable to give an overview on degradation risk in the study area, although the classification process is a crucial procedure that should be standardized for further research. Copyright © 2015 John Wiley & Sons, Ltd.